HIV prevalence among persons deprived of liberty in Brazil, 2017-2023: a time series analysis - Maria Rayssa do Nascimento Nogueira; Hévila Ferreira Gomes Medeiros Braga; Vitória Talya dos Santos Sousa; Nathanael de Souza Maciel; Emanuella Silva Joventino Melo; Patrícia Freire de Vasconcelos; Leilane Barbosa de Sousa (Epidemiologia e Serviços de Saúde)
Abstract Objective To analyze the temporal trend of the Human Immunodeficiency Virus (HIV) prevalence in the population deprived of liberty, in Brazil, between the years 2017 and 2023. Methods Time series analysis evaluation, from 2017 to 2023. The number of persons deprived of liberty and the number of HIV cases were collected from the. National Penitentiary Department Information System. In addition, sociodemographic variables were collected from each federative unit on the Atlas Brasil website concerning the National Household Sampling Survey (2021). Joinpoint software was used to calculate the annual percentage change (APC) through regressions. The relationship between HIV prevalence and indicators was analyzed in GeoDa 1.22.0.4. Results The national prevalence of HIV in persons deprived of liberty was 10.84 cases per 1,000 inmates, with an increasing trend (APC 0.3; 95%CI 0.1;0.6). This rate was higher among women (23.64/1,000 inmates), however, it showed a decreasing trend (APC 0.7; 95%CI -1.2;-0.2). However, although being lower among men (10.15/1,000 inmates), the trend in this group was increasing (APC 0.5; 95%CI 0.2;0.8). As for region, the highest prevalence was in the South (15.12/1,000 inmates). Aging rate (p-value 0.014), per capita household income (p-value 0.021) and municipal human development Index (MHDI) adjusted for income (p-value 0.024) showed positive associations. Conclusion Nationally, the prevalence was higher among women. However, while the prevalence among men showed an increasing trend, a reduction was observed among women over the period analyzed.